Preoccupation with Devotional Songs and Spiritual Well-Being of Religious Individuals: The Mediating and Moderating Effects of Religiosity and Emotionally Adaptive Functions of Music - Alexander Park; Kyung-Hyun Suh (Religions, 2022)
This study identified the relationship between preoccupation with devotional songs and spiritual well-being of religious individuals, and examined the mediating effect of intrinsic religiosity on preoccupation with devotional songs and spiritual well-being, moderated by the emotionally adaptive functions of music. The participants were 427 male and female Korean religious individuals. PROCESS Macro 3.5 Model 7 was used to analyze the moderated mediating effects. The results revealed that preoccupation with devotional songs was positively correlated with the emotionally adaptive functions of music, religiosity, and spiritual well-being, whereas emotionally adaptive functions of music were not significantly correlated with intrinsic religiosity. Intrinsic religiosity was positively correlated with spiritual well-being, whereas extrinsic social religiosity was not. In a moderated mediating model, there was a significant interaction effect of preoccupation with devotional songs and the emotionally adaptive functions of music; however, intrinsic religiosity could mediate the relationship between preoccupation with devotional songs and spiritual well-being, regardless of the level of emotionally adaptive functions of music. These findings suggest that, although there may be a slight difference depending on the level of use of emotionally adaptive functions of music, preoccupation with devotional songs can promote intrinsic religiosity and lead to the spiritual well-being of religious individuals.